Local Painting and Deformation of Meshes on the GPU. (7th August 2014) - Schäfer, H.; Keinert, B.; Nießner, M.; Stamminger, M.
<x xml:space="preserve">Abstract</x> We present a novel method to adaptively apply modifications to scene data stored in GPU memory. Such modifications may include interactive painting and sculpting operations in an authoring tool, or deformations resulting from collisions between scene objects detected by a physics engine. We only allocate GPU memory for the faces affected by these modifications to store fine‐scale color or displacement values. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>